Primary Care UK Records of Brain Tumor Signs and Symptoms - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Symptoms and signs of brain tumor in children with and without brain tumors were compared in a UK population-based retrospective analysis of primary care records by researchers at University of York and other centers in the UK.